Project-based learning: Cultivating collaborative skills in science education - Mitha Dwi Anggriani; Ilfi Intansari; Lina Indriani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This study aimed to evaluate (1) the effect of the Project-Based Learning (PjBL) method on the cooperation skills of elementary school students and (2) the significant difference in cooperation skills between students who followed PjBL and those who followed expository learning. Using a quasi-experimental design with a non-equivalent control group of fifth-grade students, this study divided the sample into two groups: the experimental group using PjBL and the control group applying the expository method. The measurement of cooperation skills was done through observation sheets, with normality and homogeneity tests to ensure the suitability of the data. Data analysis used a paired sample t-test to compare changes in cooperation skills in the same group before and after treatment, and an independent sample t-test was used to compare cooperation skills between experimental and control groups. The results showed that PjBL significantly improved students' cooperation skills compared to the expository method, with a significance value of 0.000 for both tests, which confirmed the effectiveness of PjBL in improving students' cooperation skills compared to the expository method.